Chromosomal analysis of progenies between Lilium intersectional hybrids and wild species using ND-FISH and GISH - Zhou, Mei; Yong, Xue; Zhu, Jungang; Xu, Qian; Liu, Xiaodan; Zhang, Lu; Mou, Lisha; Zeng, Lijia; Wu, Mengxi; Jiang, Beibei; Jia, Yin; Zhang, Peihua; et al. (Frontiers in Plant Science, 2024)
Introduction Intersectional hybrids in lilies possess significant breeding value, but the lack of complete lily genomes and complex genotypes pose challenges for early identification of lily hybrids. This study aimed to use intersectional hybrid cultivars as female parents and wild lilies as male parents to facilitate early identification of hybrid offsprings and enhance the efficiency and convenience of the process. Methods We investigated the nature of cross combinations using Non-denaturing Fluorescence In Situ Hybridization (ND-FISH) and Genomic In Situ Hybridization (GISH) techniques. Three novel oligonucleotide probes—Oligo-pTa794, Oligo-pITS and Oligo-telo—were developed for lily chromosome research. Results Our results demonstrated successful hybridization between wild lilies and intersectional hybrid cultivars, producing a total of 130 hybrid progenies. The combination of ND-FISH and GISH analyses effectively revealed the genomic composition of the hybrid progeny and determined the parental origin of specific chromosomes. Discussion This research provides significant guidance for lily breeding practices and offers a valuable reference for the application of ND-FISH and GISH techniques in interspecific hybridization breeding and molecular cytogenetic research across various plant species. The methods developed enable more precise, efficient, and convenient identification of hybrid offsprings.